Central Odontogenic Fibroma (WHO Type): A Case Report and Review of Literature - Subrata Talukder; Rahul Agarwal; Prashant Gupta; B S Santosh; Deepankar Misra (Wolters Kluwer Medknow Publications, 2011)
We report a case of 15-year-old boy presented with painless swelling of right side of lower jaw since 2 years. A provisional diagnosis of dentigerous cyst involving an impacted lower second premolar was concluded after clinical examination. Radiographs revealed an expanding, well demarcated radiolucency with thin, fine, straight septae, causing root resorption and displacement of adjacent teeth and the impacted tooth was pushed to the interior border of mandible. Histologically pronounced fibroblastic hypercellularity with epithelial rests and focal areas with dentinoid or cementoid material was seen, suggestive of Central Odontogenic Fibroma (WHO Type). Only eight such cases have been reported in English literature and present one is 9th case.